Effects of the Chemical Chaperone 4-Phenylbutylate on the Function of the Serotonin Transporter (SERT) Expressed in COS-7 Cells - Masayuki Fujiwara; Hikaru Yamamoto; Tatsuhiro Miyagi; Takahiro Seki; Shigeru Tanaka; Izumi Hide; Norio Sakai (Elsevier, 2013)
The serotonin transporter (SERT) is involved in various psychiatric disorders, including depression and autism. Recently, chemical chaperones have been focused as potential therapeutic drugs that can improve endoplasmic reticulum (ER) stress-related pathology. In this study, we used SERT-transfected COS-7 cells to investigate whether 4-phenylbutylate (4-PBA), a chemical chaperone, affects the membrane trafficking and uptake activity of SERT. Treatment with 4-PBA for 24 h dose-dependently increased the uptake activity of SERT. In accordance with increased SERT activity, the expression of maturely glycosylated SERT was increased, while the expression of immaturely glycosylated SERT was decreased. This finding suggests that 4-PBA increased the functional SERT with mature glycosylation via accelerating its folding and trafficking. 4-PBA also increased the activity of the C-terminus-deleted mutant SERT (SERTΔCT), which was stacked in the ER, and decreased SERTΔCT-induced ER stress, further supporting the idea that 4-PBA acts as a chemical chaperone for SERT. Imaging studies showed that fluorescence-labeled SERT was gradually and significantly translocated to the plasma membrane by 4-PBA. These results suggest that 4-PBA and related drugs can potentially affect serotonergic neural transmission by functioning as chaperones, thereby providing a novel therapeutic approach for SERT-related diseases. [Supplementary materials: available only at http://dx.doi.org/10.1254/jphs.12194FP] Keywords:: serotonin transporter, chemical chaperone, membrane trafficking, ER stress